2007
DOI: 10.1159/000107543
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of HOE642 on Two Separate Monovalent Cation Transporters in the Human Red Cell Membrane

Abstract: Residual K+ fluxes in red blood cells can be stimulated in conditions of low ionic strength. Previous studies have identified both the non-selective, voltage-dependent cation (NSVDC) channel and the K+ (Na+)/H+ exchanger as candidate pathways mediating this effect, although it is possible that these pathways represent different modes of operation of a single system. In the present study the effects of HOE642, recently characterised as an inhibitor of the K+ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…This is in agreement with earlier findings assuming the absence of the K + (Na + )/H + exchanger in the membrane of bovine RBCs [16]. It was shown that the decrease of the intracellular pH of bovine RBCs in LIS solution after the maximum is reached declines significantly lower compared to human RBCs [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with earlier findings assuming the absence of the K + (Na + )/H + exchanger in the membrane of bovine RBCs [16]. It was shown that the decrease of the intracellular pH of bovine RBCs in LIS solution after the maximum is reached declines significantly lower compared to human RBCs [16].…”
Section: Discussionsupporting
confidence: 93%
“…Donlon and Rothstein [6] decreased the extracellular ionic strength to a very low level and described the increase of the net K + loss as a triphasic response (curve with two inflection points). Starting at physiological ionic strength and reducing it, the K + (Na + )/H + exchanger is exclusively of importance to make a substantial contribution to the increase of the K + loss, at lower ionic strengths the NSVDC channel is additionally of importance, and at very low ionic strengths it seems reasonable to propose the start of an electrical break-down of the membrane [16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eryptosis may result from activation of Ca 2ϩ -permeable cation channels with subsequent increase of cytosolic Ca 2ϩ concentration (5,6,17,18,25,27,28,33,48). The increase of cytosolic Ca 2ϩ is followed by cell shrinkage due to activation of Ca 2ϩ -sensitive K ϩ channels (12,14) and subsequent exit of KCl with osmotically obliged water (36).…”
mentioning
confidence: 99%
“…The most recent data (Kucherenko et al, 2012) have shown a blocking effect of furosemide on non-selective cation channel activity in human erythrocytes. Noteworthy, a chemical blocker HOE642 inhibited (up to 40%) cation leak current in human erythrocytes in isotonic NaCl bath solution in radiotracer experiments (Bernhardt et al 2007). It suggests that cation channels could be not only activated by toxins or chemical treatment (Tosteson et al 1991;Qadri et al 2011) but they have basal activity in untreated human erythrocytes.…”
Section: Discussionmentioning
confidence: 99%